Analisis Tingkat Kepuasan Penumpang terhadap Pelayanan Trans Banyumas Koridor I - Ida Syifaul Hikmah (Jurnal Aplikasi Teknik Sipil, 2025)
Banyumas Regency launched Trans Banyumas to create a public transport system with quality services. According to data from PT Banyumas Raya Transportasi, the number of passengers in Corridor I is less than other corridors. This study aims to evaluate Trans Banyumas Corridor I service based on passenger perceptions. The method uses Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results of the IPA method research show a suitability level of 95.71% which is categorised as satisfied, while the CSI satisfaction value is 79.94% and is categorised as satisfied. The assessment results obtained 5 indicators that needed improvement and handling including, bus driver expertise and skills (X5), handrails on the bus (Hand Grip) (X6), bus passenger capacity (X11), ease of reaching the bus stop (X13), and priority seats (X15).